Thymus Degeneration and Regeneration - Duah, Maxwell; Li, Lingling; Shen, Jingyi; Lan, Qiu; Pan, Bin; Xu, Kailin (Frontiers in Immunology, 2021)
The immune system's ability to resist the invasion of foreign pathogens and the tolerance to self-antigens are primarily centered on the efficient functions of the various subsets of T lymphocytes. However, cells in the thymus are fragile and sensitive to changes in the external environment and acute insults such as infections, chemo- and radiation-therapy, resulting in thymic injury and degeneration. Though the thymus has the capacity to self-regenerate, it is often insufficient to reconstitute an intact thymic function. Thymic dysfunction causes severe immune deficiency. Thus, exploiting the mechanism of thymic regeneration would provide new therapeutic options for these settings. This review summarizes the thymus's development, factors causing thymic injury, and the strategies for improving thymus regeneration.